SOCIO-PEDAGOGICAL FUNDAMENTALS OF PREVENTIVE WORK WITH STUDENTS OF "RISK GROUP" - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2007)
The article describes psychological and pedagogical principles of interaction of school, a family and social service in perfection of social work with the pupils from the "group of risk".